Frontiers in Hardware Security and Trust Theory, Design and Practice - Chang, Chip Hong (IET Materials, Circuits and Devices Series, 2020)
This book provides a comprehensive review of emerging security threats and privacy protection issues, and the versatile state-of-the-art hardware-based security countermeasures proposed by the hardware security community. It serves as an advanced reference for researchers on current hardware security problems, challenges and solutions